Fluctuations in Teacher Efficacy during Implementation of Destreaming - Ross, John A.; McKeiver, Sharon; Hogaboam-Gray, Anne (Canadian journal of education, 1997)
Four exemplary Grade 9 mathematics teachers were followed over a year as they implemented destreaming, an externally induced reform. Implementation of the reform had an immediate negative effect on teachers' expectations about their effectiveness in the classroom. However, within the year, teachers' beliefs about their professional efficacy rebounded. The recovery was attributed to curriculum factors (acquiring evidence that students were learning), organizational culture factors (collaborating with peers and having a timetable that supported collaboration), and personal factors (avoiding negative thoughts about their effectiveness, being certain about personal goals, and drawing on teaching experience). /// Quatre enseignants chevronnés de mathématiques en 9e année ont été suivis durant un an pendant qu'ils implantaient le décloisonnement. Cette réforme, imposée de l'extérieur, a eu dans l'immédiat un effet négatif sur les attentes des enseignants quant à leur efficacité en classe. Toutefois, avant la fin de l'année, ils avaient de nouveau repris confiance dans leur efficacité professionnelle. Ce phénomène a été attribué à des facteurs reliés au programme (accumulation de preuves que les élèves apprenaient), à des facteurs associés à la culture organisationnelle (collaboration avec les pairs et mise en place d'un horaire qui favorisait celle-ci) et à des facteurs personnels (rejet des pensées négatives au sujet de leur efficacité, certitudes au sujet des objectifs personnels et mise à profit de leur expérience de l'enseignement).